"The navel-string connecting us with the world" Buber's philosophy of responsibility. - Jasiński, Karol (Filozofia Chrześcijańska, 2009)
The article presents ethical ideas of Martin Buber (1878–1965). His main feature is the connection of morality with the religiosity. Buber understood religiosity as the dialogue of God with the man in the world. His ethics is the trial of the answering Kant’s quastion – what should  I do? Morality is the choise of the valuable relation. A very important thing is a human conscience. Buber denyed the absolute worth of the moral rules and God as a lawgiver. The central idea of his morality is responsibility. The man is responsible for human beings, situations and future of God in the world. The escape from the responsibility causes the state of existential guilt. The improvemant of the man rests on the renewing of the dialogical relation with the world.